2021
DOI: 10.17113/ftb.59.03.21.7057
|View full text |Cite
|
Sign up to set email alerts
|

Blackthorn Flower Extract Impact on Glycaemic Homeostasis in Normoglycemic and Alloxan-Induced Hyperglycaemic C57BL/6 Mice

Abstract: Research background. The use of plants and their extracts in treatments of chronic diseases is widely known in traditional medicine. The aim of this study is to determine the effects of 10-day consumption of Prunus spinosa L. flower extract on blood glucose, glycaemic load, serum α-amlyase and serum insulin, in normoglycaemic and hypergycaemic (alloxan) mice model. Experimental approach. Normoglycemic and hyperglycemic (alloxan treated, 150 mg/kg body mass) C57BL/6 mice were treated daily, during 10 days, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The study on the impact of P. spinosa L. flower extract on glycemic homeostasis [3], after 10 days of treatment with flower extract, led to the improvement of glucose homeostasis in hyperglycemic rats, an effect confirmed by the test for tolerance at the orally administered glucose. In addition, an increase of 49% in serum insulin concentration and an increase of 46% in serum α-amylase activity has been observed after the period of 10-day intake of P. spinosa L. flower extract.…”
Section: Diabetes and Associated Metabolic Pathologiesmentioning
confidence: 83%
See 3 more Smart Citations
“…The study on the impact of P. spinosa L. flower extract on glycemic homeostasis [3], after 10 days of treatment with flower extract, led to the improvement of glucose homeostasis in hyperglycemic rats, an effect confirmed by the test for tolerance at the orally administered glucose. In addition, an increase of 49% in serum insulin concentration and an increase of 46% in serum α-amylase activity has been observed after the period of 10-day intake of P. spinosa L. flower extract.…”
Section: Diabetes and Associated Metabolic Pathologiesmentioning
confidence: 83%
“…In addition, an increase of 49% in serum insulin concentration and an increase of 46% in serum α-amylase activity has been observed after the period of 10-day intake of P. spinosa L. flower extract. Based on their study, the authors in [3] have claimed for the first time that P. spinosa L. flower extract has a potential in the management of hyperglycemia. This potential is based on the bioactive compounds present in P. spinosa L. flowers that can improve glucose tolerance and insulin secretion and decrease serum α-amylase activity.…”
Section: Diabetes and Associated Metabolic Pathologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The data confirmed that short-term (in minutes) or long-term (for 10 days) oral consumption of blackthorn flower extract can slightly but significantly raise blood sugar concentration in metabolically healthy (normoglycemic) mice. Consuming blackthorn flower extract for 10 days reduced blood glucose levels, in C57BL/6 mice, it improved glucose tolerance, boosted insulin production, and reduced serum α-amylase activity, which may have hyperglycemic protective benefits [94].…”
Section: Antidiabetic Effectmentioning
confidence: 99%